2013
DOI: 10.1371/journal.pone.0064914
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Copayments for Prescriptions on Adherence to Prescription Medicines in Publicly Insured Populations; A Systematic Review and Meta-Analysis

Abstract: IntroductionCopayments are intended to decrease third party expenditure on pharmaceuticals, particularly those regarded as less essential. However, copayments are associated with decreased use of all medicines. Publicly insured populations encompass some vulnerable patient groups such as older individuals and low income groups, who may be especially susceptible to medication non-adherence when required to pay. Non-adherence has potential consequences of increased morbidity and costs elsewhere in the system.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 46 publications
1
64
0
1
Order By: Relevance
“…9,[12][13][14] We have attempted to bolster previous approaches by determining the increase in likelihood of adherence based on copayment using 2 distinct adherence thresholds and also by determining the incremental change in adherence caused by copayment in a retrospective cohort of new users of statins in the Veterans Health Administration (VHA).…”
mentioning
confidence: 99%
“…9,[12][13][14] We have attempted to bolster previous approaches by determining the increase in likelihood of adherence based on copayment using 2 distinct adherence thresholds and also by determining the incremental change in adherence caused by copayment in a retrospective cohort of new users of statins in the Veterans Health Administration (VHA).…”
mentioning
confidence: 99%
“…Co-payments were introduced as a revenue raising measure. Two Irish studies found both co-payments (€0.50 and €1.50) were associated with larger reductions in adherence to less--essential medicines than essential medicines, with anti-depressant and anxiolytic/hypnotic medicines being the exception [34,35]. In 2013, a number of cost containment measures were introduced.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a significant change in slope (-1.1%, 95% CI -1.9 to -0. 4) indicated that adherence fell in the months following the policy change (Table 2). …”
Section: Anti-hypertensive Drugsmentioning
confidence: 99%
“…[1][2][3] Most studies have found that as the price of the copayment increases, patients reduce their adherence to essential life-prolonging drugs that are used in the treatment of chronic disease. [1,4,5] Copayments for prescription drugs are therefore directly and indirectly associated with increased morbidity, mortality and increased health care costs. [3,[6][7][8] While the results of previous research on copayments are mostly consistent, the majority of studies included in existing systematic reviews have been conducted in the U.S. and Canada.…”
Section: Introductionmentioning
confidence: 99%